The Influence Of Motivation, Product Completeness, And Cashback On Consumers’ Purchase Decisions In E-Commerce - Sri Mulianingsih; Dessy Hutajulu (Jurnal Ilmiah Multidisiplin, 2025)
E-commerce platforms as a modern shopping lifestyle have become increasingly widespread as a result of developments in information technology in recent years. The purpose of this study is to analyze the influence of Motivation, Product Completeness, and Cashback on Purchase Decisions in E-Commerce. The analytical method in this study uses primary quantitative data, and the testing stages conducted include validity testing, reliability testing, normality testing, heteroscedasticity testing, multicollinearity testing, multiple regression analysis, t-test, F-test, and the coefficient of determination (R²). The data used in this study were collected using a questionnaire instrument, and valid data were successfully obtained from 96 respondents. The sampling method used in this study is non-probability sampling with a purposive sampling technique. The analytical tool used is SPSS version 25. Based on the research results, the classical assumption test results show that the regression model is normally distributed, with the obtained equation: Y = −0.483 + 0.407X₁ + 0.344X₂ + 0.505X₃ + e. The classical assumption test results indicate that the regression model is normally distributed, free from multicollinearity, and free from heteroscedasticity. In the partial (t) test, each variable—Consumer Motivation, Product Completeness, and Cashback—has an effect on Purchase Decisions in E-Commerce. In the F-test, all independent variables simultaneously influence purchase decisions. Based on the output results above, the adjusted R-square coefficient of determination is 0.593 or equal to 59.3%, and the remaining 40.7% is influenced by other variables outside those used in this study.